Activity of Ukrainian militia in 1941-1945: usage of experience in modern conditions - Тимченко, Анатолій Павлович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2015)
Considering positive and negative experience of Ukrainian militia’s activity in 1941-1945, the author of the article suggests priority actions to enhance and improve the quality of functioning of Ukrainian enforcement agencies in the extreme conditions of war in the fight against a strong and cruel enemy of the Ukrainian people. Careful analysis of national interests and peculiarities of historical development of national and foreign practice convinces that it is necessary to reorganize Ukrainian militia in a completely different executive body – police. A modern state and situation in Ukraine is analyzed. The author believes that militia will be reorganized; its staff will be joined by smart, honest and true patriots of Ukraine and very soon it will become police. The author is also sure that Ukraine will win in this war with Russia; Putin will be brought to the Hague tribunal as well as other dictators. The head of Russian regime should realize that nor intimidation neither lying, destroying cities and villages and their infrastructure and population, or huge numbers of modern weapons influence the greatness of a country. Its power depends on economic potential, people’s knowledge, and their ability to invent something new, create and export high quality goods and products. The author notes that unfortunately lots of European countries do not understand what is really going on in Ukraine right now and states that they are wrong thinking that it is civil war. It is actually a war against the most powerful on the European continent Russian army.